Pressure-induced monotonic enhancement of T c to over 30 K in superconducting Pr0.82Sr0.18NiO2 thin films - N. N. Wang; M. W. Yang; Z. Yang; K. Y. Chen; H. Zhang; Q. H. Zhang; Z. H. Zhu; Y. Uwatoko; L. Gu; X. L. Dong; J. P. Sun; K. J. Jin; et al. (Nature Communications, 2022)
Despite much recent effort, the highest reported T c of the infinite-layer nickelates remains lower than 15 K. Here, the authors apply pressure to Pr0.82Sr0.18NiO2 thin films and observe a monotonic increase of T c to 31 K at 12.1 GPa, an increase that does not level off with increasing pressure.